Analysis of the Effect of Reduced Corporate Income Tax Implementation on Employment in Turkey - Elyasa Aksoy (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This paper investigates the effect of regional differences in corporate income tax reduction rates on employment within the scope of the reduced corporate income tax implementation put into effect in 2009. The implementation aims to encourage and increase investments, production, employment, and large-scale investments to increase international competitiveness, foreign direct investment and support Research and Development (R&D) activities, and eliminate regional development differences by reducing corporate income tax rates by region. This paper focuses on employment outcome in particular. The analysis relies on the "TurkStat Household Labor Force Survey Micro Dataset" in 2004-2021 for Turkey. Difference in Differences (DID) and Difference in Differences with Propensity Score Matching (DID-PSM) methods were used in the impact analysis of the tax policy discussed in the study. We employ DID and DID-PSM methods, designating respondents in regions with the highest corporate income tax reduction rates as treated subjects, and those with the lowest corporate income tax reduction rates as control subjects. The effects of regional differences in corporate income tax reduction rates on employment have been empirically demonstrated. The findings show that the regional differences in corporate income tax reduction rates on employment significantly and positively affect employment.